The management of post-traumatic elbow extension deficit in the subacute phase: A case report series of four patients - Germaine Sim; Jennifer Fleming; Celeste Glasgow (Proceedings of Singapore Healthcare)
Study design Case report series using a using a mixed-methods design. Introduction There is a lack of high-quality evidence regarding the efficacy of orthotic intervention compared to standard care to resolve elbow contractures in the early stages after trauma. Purpose To present the results of four post-traumatic elbow patients with extension deficits in the subacute rehabilitation phase. Methods Four patients met the eligibility criteria and were randomly allocated to a 6-week extension orthotic (Orthotic1-2) or standard care (Control3-4). All participants received 6 weekly therapy sessions which included a standardized home exercise program. Orthotic1-2 received additional extension orthoses which were remoulded each week according to progress. Outcome measures were collected at baseline and final assessment by a blinded assessor including extension AROM and PROM, pain Numeric Rating Scale (NRS), Patient Rated Elbow Evaluation (PREE), Oxford Elbow Scale (OES) and Global Rating of Change (GRC). All participants had their weekly ROM recorded by their treating therapists. Short qualitative interviews were conducted with Orthotic1-2 at the final review. Results Plots of extension measures demonstrate participants’ response to the weekly treatments. All participants demonstrated clinically important improvements in extension AROM, extension PROM, OES-Function and GRC scores. Qualitative data on patient factors affecting orthotic use are described. Discussion The four cases provide descriptive data on early orthotic intervention and standard care in post-traumatic elbow patients with extension deficits over a 6-week period. While orthotic intervention was well-received, further research with a larger sample size is warranted to explore the role of extension orthoses in traumatic contractures.